The Effect of SAQ (Speed, Agility, Quickness) Training on Handball Player Performance - Raden Farrel Faizal Ramadhan; Yopi Meirizal; Rama Adha Septiana (STKIP Pasundan Press, 2026)
This study aims to analyze the effect of SAQ (Speed, Agility, Quickness) training on the performance of handball players in the Handball Student Activity Unit (UKM) at STKIP Pasundan Cimahi, particularly in improving speed, agility, and reaction time. The research employed an experimental method with a One Group Pretest-Posttest design, involving 10 participants selected through purposive sampling. The instrument used was the Illinois Agility Test. Data analysis was conducted using the Paired Sample t-Test to compare pretest and posttest results, preceded by a Shapiro-Wilk normality test. If the data were not normally distributed, the Wilcoxon test was used as an alternative. Based on the results, it can be concluded that SAQ (Speed, Agility, Quickness) training had a significant effect on improving the performance of the handball players. This was evidenced by an improvement in the average test scores, from 24.90 seconds in the pretest to 19.764 seconds in the posttest, indicating enhanced performance, as lower scores in the Illinois Agility Test reflect faster times and better ability. Furthermore, the statistical test results showed a significant difference between the two sets of scores (p = 0.000). The majority of participants experienced performance improvement after undergoing SAQ training, proving the effectiveness of this training method in developing speed, agility, and quickness in handball players.